Primary echinococcal cyst in the axillary region - Ozsoy, Mustafa; Keles, Celalettın; Kahya, Mumtaz; Keles, Gonul (The Journal of Infection in Developing Countries, 2011)
Introduction: Human hydatid disease is a parasitic infection caused by the larval form of Echinococcus granulosus. It has worldwide distribution and is endemic in many countries, especially the Mediterranean region. It most commonly affects the liver and lungs although multi-organ involvement has been observed in 20-30% of patients. Case report: A 45-year-old woman presented to a gynaecologist because of a mass in the axillary region. Her mother and her two sisters were undergoing treatment for breast cancer. In her examination, a hard, semi-mobile, painless mass was found that was approximately 3 cm in diameter. Axillary ultrasonography showed lymphadenopathy. No abnormality was found in mammographic examination of either breast, or in abdominal ultrasonography and chest X-ray. Occult breast cancer was suspected but when the mass was excised for pathological examination the biopsy showed a hydatid cyst with germinative membranes. Subsequent lung, abdomen and brain tomography scans, whole body bone scintigraphy and hydatid serology, including indirect haemagglutination and enzyme-linked immunosorbent assay, were negative. For these reasons an isolated axillary hydatid cyst was diagnosed. Conclusion: Parasitic cysts should be considered in endemic areas in patients presenting with a soft tissue mass in the axillary region. Imaging methods should be planned to include this possibility.